2020
DOI: 10.2147/jep.s259328
|View full text |Cite
|
Sign up to set email alerts
|

<p>Ultra Long-Acting β-Agonists in Chronic Obstructive Pulmonary Disease</p>

Abstract: Introduction Inhaled β-agonists have been foundational medications for maintenance COPD management for decades. Through activation of cyclic adenosine monophosphate pathways, these agents relax airway smooth muscle and improve expiratory airflow by relieving bronchospasm and alleviating air trapping and dynamic hyperinflation improving breathlessness, exertional capabilities, and quality of life. β-agonist drug development has discovered drugs with increasing longer durations of action: short acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 121 publications
0
3
0
2
Order By: Relevance
“…Protokylol, a β2-adrenergic agonist used as a bronchodilator [57] emerged as a compound with the second highest probability of exerting agonist activity on TRPV1. Two different, overlapping binding sites were observed for protokylol, one specific to vanilloids and competitive antagonists and another for phosphoinositides [59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protokylol, a β2-adrenergic agonist used as a bronchodilator [57] emerged as a compound with the second highest probability of exerting agonist activity on TRPV1. Two different, overlapping binding sites were observed for protokylol, one specific to vanilloids and competitive antagonists and another for phosphoinositides [59].…”
Section: Discussionmentioning
confidence: 99%
“…Bronchodilator protokylol [57] showed the second highest estimated probability for acting as a TRPV1 agonist. Protokylol had an average activity score of 2.76, its molecule containing the 5-(5-cyclohexylpentyl)-octahydro-1H-indene BM skeleton (BM-126), represented by the benzene (PR-1) and benzodioxole (PR-44) plain rings, these structural features being also present among TRPV1 agonists.…”
Section: Prediction Of Potential Trpv1 Modulators Through Drugmentioning
confidence: 99%
“…Вилантерол обладает высокой селективностью к β 2 -адренорецепторам. По данным исследований, его селективность выше, чем у сальбутамола, формотерола, индакатерола, и сходна с салметеролом [25][26][27]. В исследованиях показано, что после ингаляции вилантерола средняя C max достигалась через 5-15 мин, абсолютная биодоступность ингаляционного вилантерола составляла около 27%.…”
Section: особенности препарата вилантерол/умеклидиниумunclassified
“…В исследованиях показано, что после ингаляции вилантерола средняя C max достигалась через 5-15 мин, абсолютная биодоступность ингаляционного вилантерола составляла около 27%. In vitrocвязывание с белками плазмы крови человека в среднем составляет 94% [26]. В клинических исследованиях применение вилантерола в дозе 25 мкг у пациентов с ХОБЛ в первый день приема уже через 6 мин увеличивало ОФВ 1 на > 100 мл от исходного [28].…”
Section: особенности препарата вилантерол/умеклидиниумunclassified
“…Numerous ULABA drugs have been developed and studied in clinical trials, some which show promising bronchoprotective effects, however, others have been shown to adversely affect the heart 275 . Long acting muscarinic antagonists (LAMAs) are also used as bronchodilators in asthmatics, as they block cholinergic signaling from nerves and reduce airway tone 276 , but studies have demonstrated that they can impair ciliary beating, increasing infection and mucus plugs 277 .…”
Section: Bronchodilatorsmentioning
confidence: 99%